Pemberdayaan Masyarakat Desa Karang Asem Timur dalam Optimalisasi Budi Daya Ikan dan Produk Olahannya - Laily Dwi Arsyianti; Furqon Syarief Hidayatulloh; Fajar Maulana (Institut Pertanian Bogor, 2022)
In early 2020, Karang Asem Timur Village received a grant from the Ministry of Marine Affairs in the form of a catfish farming system in buckets (budikdamber). This program is conducted by several business groups that are widely spread in the community. Many of the catfish farmers in Karang Asem Timur Village complain about the high cost of commercial feed which is commonly used, made the profits earned very insignificant and even tend to lose, thus need supervision. The IPB Serving Lecturer Program attempts to empower the people of Karang Asem Timur Village in optimizing fish farming activities and their processed products. This program as an extension of the Thematic Field Apprenticeship Lecture (KKN-T) program, partners with the catfish business group in Karang Asem Timur Village look for other feeding alternatives that are cheaper and have good nutritional content for catfish. In addition, the program also cooperates with youth organizations and family welfare empowerment to open business opportunities for processed catfish products and catfish cultured products. It is hoped that the progress and independence of the village economy can be achieved. The society eagerly participate and propose for the program to be continued gradually and sustainably in the near future.